Conflict of laws in a globalized world. - Von Mehren, Arthur Taylor; Gottschalk, Eckart (Cambridge University Press, 2007)
This book contains ten contributions that examine current topics in the evolving transatlantic dialogue on the conflict of laws. The first five contributions deal with the design of judgments conventions in general, the recently adopted Hague Convention on Choice of Court Agreements, problems involving negative declaratory actions in international disputes, and recent transatlantic developments relating to service of process and collective proceedings. The remaining five contributions focus on comparative and economic dimensions of party autonomy, choice of law relating to intellectual property rights, the applicable law in antitrust law litigation, international arbitration, and actions for punitive damages.